Technologies transfer as a part of the process of executive staff professional development in the sphere of education - Lunyachek, V. (Problems of Engineer-Pedagogical Education, 2018)
This paper highlights modernization of the process of executive staff professional development in the sphere of education through pedagogical and management technologies transfer. The relevance is proved based on a number of sources analysis covering administrative and pedagogical technologies, where emphasis is put on the structure and content of technologies, but not on their presentation by consumer. It is presented estimated working training program for professional executive staff development, which involves mastering of the quality education management technique in the education establishments. The emphasis is put on the legal and regulatory framework provision while technology transfers in the field of education, including contract law application. It is reflected the specific features of the distance component implementation in professional executive staff development using Moodle (distance learning system). It is analysed specific features of its content preparation in relation to specifics of professional development process, where technology transfer is its component.